THE ROLE OF MASS MEDIA IN THE 2019 SIMULTANEOUS GENERAL ELECTION - Adi Munasip (NOMOI Law Review, 2021)
Mass media plays an important role in the development of democracy in Indonesia. Mass media in addition to being an institution that provides information, but also acts as an institution that provides education to the community. The method used in this paper is normative juridical legal research. Mass media in elections have a fairly important role, because mass media can provide information to the public. And it can also make it easier for candidates to be elected during the 2019 simultaneous elections by going through campaigns, political ads in the media, or can interact through the media. Media can also be easier to provide access for those who need information.However, the role that can be carried out by the media in elections, but the concern is that the media must be returned to its function as a pillar of democracy and education. Keyword: Mass Media, General, Election.